Ökonomische Überlegungen zur Kameraüberwachung als Maßnahme gegen den Terrorismus - Alois Stutzer; Michael Zehnder (University of Basel, Center of Business and Economics (WWZ), 2009)
– In recent times, camera surveillance or closed-circuit television (CCTV) as an instrument potentially deterring crime and terrorism has become a focus of the public discourse. CCTV might be the most rapidly spreading and, at the same time, one of the most disputed measures of contemporary public security policy. This article presents theoretical arguments and empirical results that need to be considered in plans of future CCTV schemes as well as in methodically challenging CCTV evaluations. Previous evidence shows that the effectiveness of this situational crime prevention instrument is substantially depending on the context within which it is implemented. According to a comparative economic analysis of illegal behavior, we expect a relatively smaller deterrent effect of CCTV on terrorism than on other forms of crime. On the one hand, terrorists can switch to numerous alternative targets not monitored by cameras. On the other hand, CCTV images raise the degree of publicity terrorists can achieve.
Keywords: 330; Messtechnik; Videogerät; Terrorismus; Kriminalität; Wahrnehmung